Wujud Campur Kode Takserumpun dalam Wacana Berita Daerah Harian Suara Merdeka - Mujid Farihul Amin (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Language events that often occur in daily interactions are the mixing of a code/ element of language into the code/element of another language. These linguistic events in sociolinguistics are known as mixed codes. Based on the language of the source, the mixed code in the Suara Merdeka daily news discourse can be divided into two types, namely the cognate mixed code and the noncognate mixed code. In this paper, only the noncognate mixed code. In the noncognate mixed code, between the source language and the target language have no relationship, both geographically and genetically. So, geographically these languages are used as an introduction to different political areas. Likewise seen from their kinship relations, the languages involved in interfering with the code are not related. The form of noncognate mixed code contained in Suara Merdeka's daily regional news discourse can be in the form of words, phrases, forms of baster, idioms, and clauses.